Chemical manipulation of growth and flowering in potted Melastoma decemfidum and Tibouchina semidecandra - Abdullah, Thohirah; Malek, Asiah A.; Ahmad, Siti H. (International Society for Horticultural Science (ISHS), 1998)
Melastoma decemfidum and Tibouchina semidecandra are ornamental shrubs traditionally planted in gardens for their attractive foliage and flowers. Both plant species are also grown for their medicinal properties. More recently, interest in potted Melastoma and Tibouchina has increased and this study was conducted to determine the effects of the growth retardants, paclobutrazol and flurprimidol on their growth and flowering responses. Both growth retardants were applied as soil drenches at concentrations of 0, 1000, 2000, 3000, and 4,000 mg L-1 for paclobutrazol and 0, 50, 100, 150, and 200 mg L -1 for flurprimidol. Paclobutrazol decreased plant height, internode length, number of internodes and root dry weight for both plant species but all concentrations of paclobutrazol tested were too high, and unsuitable for producing saleable plants. Flurprimidol was more suitable in controlling plant growth and flowering of M. decemfidum and T. semidecandra. At 50 mg L -1 flurprimidol effectively reduced plant height and shortened the time for production of the first flower for both species, and increased total number of flowers produced by M. decemfidum.